Non-photoreceptor Expression of Tulp1 May Contribute to Extensive Retinal Degeneration in Tulp1-/- Mice - Humphries, Peter; Farrar, Gwyneth; Hokamp, Karsten (My University, 2020)
Mutations in tubby like protein 1 gene (TULP1) are causative of early-onset recessive inherited retinal degenerations (IRDs); similarly, the Tulp1-/- mouse is also characterized by a rapid IRD. Tulp1 mRNA and protein expression was analyzed in wild type mouse retinas and expression data sets (NCBI) during early postnatal development. Comparative histology was undertaken in Tulp1-/-, rhodopsin-/- (Rho-/-) and retinal degeneration slow-/- (Rds-/-) mouse retinas. Bioinformatic analysis of predicted TULP1 interactors and IRD genes was performed. Peak expression of Tulp1 in healthy mouse retinas was detected at p8; of note, TULP1 was detected in both the outer and inner retina. Bioinformatic analysis indicated Tulp1 expression in retinal progenitor, photoreceptor and non-photoreceptor cells. While common features of photoreceptor degeneration were detected in Tulp1-/-, Rho-/-, and Rds-/- retinas, other alterations in bipolar, amacrine and ganglion cells were specific to Tulp1-/- mice. Additionally, predicted TULP1 interactors differed in various retinal cell types and new functions for TULP1 were suggested. A pilot bioinformatic analysis indicated that in a similar fashion to Tulp1, many other IRD genes were expressed in both inner and outer retinal cells at p4–p7. Our data indicate that expression of Tulp1 extends to multiple retinal cell types; lack of TULP1 may lead to primary degeneration not only of photoreceptor but also non-photoreceptor cells. Predicted interactors suggest widespread retinal functions for TULP1. Early and widespread expression of TULP1 and some other IRD genes in both the inner and outer retina highlights potential hurdles in the development of treatments for these IRDs.
PUBLISHED
cited By 1
Keywords: Retina; Degeneration; Mouse model; Inherited; Tulp1; Disease; Blindness; Eye